'Tom Tiver, Tom Tiver met Yallery Brown …': Drama and the dark side of traditional tales. Issue 2 (2nd July 2016) - Winston, Joe
Abstract: This article gives an account of a drama based around an adaptation of the English folk tale Yallery Brown which was used to explore drugs related issues. The account is framed by a consideration of the problems and possibilities presented by the darker images that so often characterise traditional tales. Particular attention is paid to the moral agendas within the work in an attempt to investigate if they are as contradictory as at first they might appear.